2010
DOI: 10.1007/s11060-010-0417-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of tumour and surgical treatment in glioma patients

Abstract: Quality of life in brain tumour patients is an emerging issue and has prompted neurosurgeons to reconsider the need for cognitive assessment in the course of treatment. In particular, to date there has been a lack of comprehensive neuropsychological assessment performed preoperatively and in the acute postoperative period. We examined 29 patients with glioma, analysing several functional domains-intelligence, executive functions, memory, language, praxis, gnosis and mood state-in order to establish the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(152 citation statements)
references
References 31 publications
5
144
1
2
Order By: Relevance
“…Brain tumor patients are a particularly vulnerable population, in which clinicians need to be aware of challenges of informed consent due to their underlying diseaserelated impairment [17]. One study found that subjects frequently consent to treatment with only modest appreciation of the risks involved, with 23.9% of subjects reporting no risks despite being explicitly informed otherwise [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain tumor patients are a particularly vulnerable population, in which clinicians need to be aware of challenges of informed consent due to their underlying diseaserelated impairment [17]. One study found that subjects frequently consent to treatment with only modest appreciation of the risks involved, with 23.9% of subjects reporting no risks despite being explicitly informed otherwise [18].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that subjects frequently consent to treatment with only modest appreciation of the risks involved, with 23.9% of subjects reporting no risks despite being explicitly informed otherwise [18]. Specifically, patients with brain tumors may have altered cognition and may lack the capacity to understand a rigorous informed consent process that covers several concurrent trials [17]. In other vulnerable populations, patients with a thought disorder, willingness to participate in trials was correlated with higher education and lower cognitive impairment [19].…”
Section: Introductionmentioning
confidence: 99%
“…They both underwent a preliminary multidisciplinary interview as well as a battery of psychological and neuropsychological tests (Table 1) before and after surgery. 12,14,15 In addition to general neuropsychological testing, assessments of their spatial abilities and spatial neglect in particular were performed. 4 We followed the standard rules to assess spatial neglect: for all the paper-and-pencil tests, the sheet of paper was preoperatively centered to the patient's sagittal head plane, and no time limit was given for task execution (except for the Diller Letter Cancellation Test, when the time limit was 2 minutes).…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have already highlighted the importance of neuropsychological testing before, during, and after glioma surgery. 22,98,114,124 The clinical relevance of monitoring other cognitive functions like calculation 20 has been shown. Navigated TMS is not only able to map function but also to modulate it.…”
Section: Fig 5 This Neuronavigational Screenshot Shows a Large Insumentioning
confidence: 99%